Integrating Quality Function Deployment (QFD) In The Hygienic Oil-Draining Tools For Msmes: a Consumer-Centered Approach - Damas Aulia Nata; Hamdan Hamdan; Ryando Rama Haiban (Jurnal Riset Ilmu Teknik, 2024)
Purpose – This study aims to design an oil-draining spinner tailored for Micro, Small, and Medium Enterprises (MSMEs) using the Quality Function Deployment (QFD) approach to ensure ergonomics, hygiene, and consumer-oriented innovation. Design– A quantitative descriptive design was applied, involving observations, interviews, and structured questionnaires with 10 MSME owners in fried food production. Consumer requirements were systematically translated into technical attributes through the House of Quality (HOQ). Reliability and validity testing were conducted, followed by concept screening and scoring to determine the optimal design. Findings – The results highlight that consumers prioritize minimalist size, multifunctionality, durability, and ease of cleaning. Correlation analysis revealed strong relationships between consumer needs and technical attributes, with system effectiveness and process stability being the most influential. Comparative evaluation of design alternatives identified a hybrid material combination of wood and heat-resistant plastic as the most feasible solution, offering balance between functionality, hygiene, and ergonomics. Practical implications – The findings provide MSMEs with a practical tool to improve food safety, durability, and competitiveness. The results also serve as a reference for policymakers in supporting MSME innovation through affordable, consumer-driven technologies. Originality/value – Unlike previous studies limited to prototypes, this research integrates consumer validation into QFD-based design, bridging gaps between technical feasibility and real-world MSME applications.